Frequency of tuberculous and non-tuberculous mycobacteria in HIV infected patients from Bogota, Colombia - León Clara I; Gómez Bertha; de Mendivelson Ellen; Bustillo José G; Alvarado Fernando S; Gómez-Marin Jorge E; Murcia-Aranguren Martha I; Triana William A; Vargas Erwing A; Rodríguez Edgar (BMC Infectious Diseases, 2001)
Abstract Background The prevalence of infections by Mycobacterium tuberculosis and non-tuberculous Mycobacterium species in the HIV-infected patient population in Colombia was uncertain despite some pilot studies. We determined the frequency of isolation of Mycobacterium tuberculosis and of non-tuberculous Mycobacterium species in diverse body fluids of HIV-infected patients in Bogota, Colombia. Methods Patients who attended the three major HIV/AIDS healthcare centres in Bogota were prospectively studied over a six month period. A total of 286 patients were enrolled, 20% of them were hospitalized at some point during the study. Sixty four percent (64%) were classified as stage C, 25% as stage B, and 11% as stage A (CDC staging system, 1993). A total of 1,622 clinical samples (mostly paired samples of blood, sputum, stool, and urine) were processed for acid-fast bacilli (AFB) stain and culture. Results Overall 43 of 1,622 cultures (2.6%) were positive for mycobacteria. Twenty-two sputum samples were positive. Four patients were diagnosed with M. tuberculosis (1.4%). All isolates of M. tuberculosis were sensitive to common anti-tuberculous drugs. M. avium was isolated in thirteen patients (4.5%), but only in three of them the cultures originated from blood. The other isolates were obtained from stool, urine or sputum samples. In three cases, direct AFB smears of blood were positive. Two patients presented simultaneously with M. tuberculosis and M. avium. Conclusions Non-tuberculous Mycobacterium infections are frequent in HIV infected patients in Bogota. The diagnostic sensitivity for infection with tuberculous and non-tuberculous mycobacteria can be increased when diverse body fluids are processed from each patient.